2023
DOI: 10.3847/2041-8213/ace4ca
|View full text |Cite
|
Sign up to set email alerts
|

SN 2023ixf in Messier 101: A Variable Red Supergiant as the Progenitor Candidate to a Type II Supernova

Abstract: We present preexplosion optical and infrared (IR) imaging at the site of the type II supernova (SN II) 2023ixf in Messier 101 at 6.9 Mpc. We astrometrically registered a ground-based image of SN 2023ixf to archival Hubble Space Telescope (HST), Spitzer Space Telescope (Spitzer), and ground-based near-IR images. A single point source is detected at a position consistent with the SN at wavelengths ranging from HST R band to Spitzer 4.5 μm. Fitting with blackbody and red supergiant (RSG) spectral energy distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
68
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(83 citation statements)
references
References 107 publications
(119 reference statements)
15
68
0
Order By: Relevance
“…Overall, both the confined high-density CSM shell and the extended lowdensity wind may have made the RSG progenitor star quite dust obscured prior to the explosion (Davies et al 2022). This is consistent with the findings of Kilpatrick et al (2023) who show that the pre-explosion Hubble and Spitzer imaging of SN 2023ixf indicates a moderately sized (∼11 M e ) RSG progenitor star enshrouded in a dust shell.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, both the confined high-density CSM shell and the extended lowdensity wind may have made the RSG progenitor star quite dust obscured prior to the explosion (Davies et al 2022). This is consistent with the findings of Kilpatrick et al (2023) who show that the pre-explosion Hubble and Spitzer imaging of SN 2023ixf indicates a moderately sized (∼11 M e ) RSG progenitor star enshrouded in a dust shell.…”
Section: Discussionsupporting
confidence: 88%
“…We performed point-spread-function (PSF) photometry with the DOLPHOT package (Dolphin 2000) and detected the progenitor significantly in the F658N, F675W, and F814W bands. The measured magnitudes, which are listed in Table 1, are slightly brighter than those reported by Kilpatrick et al (2023) within 1σ-4σ uncertainties (note their magnitudes are in the AB system). The difference could be due to our different parameters in DOLPHOT photometry, and this difference does not have any significant effect in the following analysis.…”
Section: Hst Optical Datamentioning
confidence: 55%
“…We retrieved the calibrated images from the Mikulski Archive for Space Telescopes 7 and reprocessed them with the ASTRO-DRIZZLE package (Hoffmann et al 2021) for better image alignment and cosmic ray removal. On the ACS F814W image, there are two objects within 0 2 from the reported SN position and Kilpatrick et al (2023) identified the relatively brighter one as the SN progenitor (Figure 1) based on differential astrometry with postexplosion images. We performed point-spread-function (PSF) photometry with the DOLPHOT package (Dolphin 2000) and detected the progenitor significantly in the F658N, F675W, and F814W bands.…”
Section: Hst Optical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The high-resolution spectroscopy revealed that the confined CSM is asymmetric (Smith et al 2023). Preimaging data have been analyzed at the SN 2023ixf site in recent works, constraining the mass of the progenitor to between 12 and 17 M e (Jencson et al 2023;Kilpatrick et al 2023;Pledger & Shara 2023;Soraisam et al 2023). These estimates are well within the earlier detected CCSN progenitors (Smartt 2009;Van Dyk 2017).…”
Section: Introductionmentioning
confidence: 99%